THE IMPACT OF THE INCREASE IN FUEL ON THE INCOME OF SMEs IN KARANGBESUKI KELURAHAN MALANG - Risnaningsih Risnaningsih; Dyah Agustin Widhi Yanti; Poopy Indrihastuti; Agus Kusnanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Micro, small and medium enterprises (MSMEs) are one of the business fields that can develop and be consistent in the national economy. Micro, small and medium enterprises (MSMEs) are a good platform for job creation and can absorb a large number of workers, especially during a crisis, as well as in terms of their contribution to the formation of regional output growth. The aim of this research is to examine the impact of rising fuel prices on the income of micro, small and medium enterprises (MSMEs) in Karangbesuki Malang. In this study using quantitative methods, namely analyzing and interpreting the relationship between variables through accurate and up-to-date data according to the problems in this study using simple linear regression analysis. that the increase in fuel prices resulted in a corresponding increase in the prices of goods and services, hampered the public production process due to rising prices, as well as decreased public purchasing power and inflation. Thus, the increase in fuel prices will have a negative impact on the economy of the wider community. This has been proven in this study, where the results of the analysis of the research data (t test) show that the sig t value is smaller than the specified significance value (0.017